The influence of weeds on soybean yield - Felicia Chețan; Raluca Rezi; Camelia Urdă; Cornel Chețan; Alina Șimon; Marius Bărdaș; Adrian Ceclan; Ioan Gaga (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The research was carried out at the Turda Agricultural Research and Development Station (ARDS), located in the hilly area of Transylvania and followed the influence of weed infestation on the Felix soybean variety yield, grown in two tillage systems (CS-conventional-plow, NT- unconventional-direct seeded). Sowing was done at 65 bg/m2 , the distance between rows being 18 cm. From the results obtained, in six experimental years (2017-2022), it was concluded that, in the climatic and soil conditions of Turda, soybean is less suitable for cultivation in the NT system, noting an increase in the infestation of the soil with weeds, especially with perennial species, but also a significant reduction in yield compared to the conventional system (CS).
Keywords: Q01; Q15; Q16; 330; weeds; tillage system; clime; soybean; yield